STRATEGI PEMBANGUNAN DAN PENGEMBANGAN PERMUKIMAN (SPPIP) DALAM PENANGANAN PERMUKIMAN KUMUH DI JAWA TIMUR - Niken Dyah Nawang Wulan; Andre prasetyo widodo (Bahasa Indonesia, 2020)
Slums are areas that were born because of development failure, poverty and high population density. As we know, slums do not meet the criteria for habitation. This research will discuss how the development strategy and development of settlement infrastructure by local governments in handling slums in East Java. This Study uses a qualitative method by means of descriptive analysis through data obtained from literatur studies. The result of the literatur study are comparative government programs from two regions namely Sidoarjo Regency and Malang city. Based on the result of a comparative study of the two regions, it can be seen the implementation of the KOTAKU (City Without Slums) program and the achievements that have been obtained by the two regions.